Wright, African Americans In The Early Republic, 1780-1831 - Adebayo, A.G. (Teaching History: A Journal of Methods, 1994)
Every new addition to the literature on the African-American experience has something unique-some offer new information based on altogether new primary source materials, others bring fresh insights into what is already known about a particular subject through a reinterpretation of available data, still others attempt to synthesize available pieces of evidence and interpretations and make them more accessible. Donald Wright's new book, African Americans in the Early Republic, 1789-1831, belong to the last category. It is a work of synthesis, well conceived and well executed.